2006
DOI: 10.1631/jzus.2006.b0279
|View full text |Cite
|
Sign up to set email alerts
|

Performance of underground heat storage system in a double-film-covered greenhouse

Abstract: An underground heat storage system in a double-film-covered greenhouse and an adjacent greenhouse without the heat storage system were designed on the basis of plant physiology to reduce the energy consumption in greenhouses. The results indicated that the floor temperature was respectively 5.2 °C, 4.6 °C and 2.0 °C higher than that of the soil in the adjacent reference greenhouse after heat storage in a clear, cloudy and overcast sky in winter. Results showed that the temperature and humidity were feasible fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The simulation results were compared with their previous measured data and were found to be in very good agreement [39]. Wang and Liang [40] reported the performance of underground heat storage systems for greenhouse application by using a GHE. The system was designed to handle low ambient temperature during the nighttime which affected the crops.…”
Section: Agricultural Greenhouse Coolingmentioning
confidence: 57%
“…The simulation results were compared with their previous measured data and were found to be in very good agreement [39]. Wang and Liang [40] reported the performance of underground heat storage systems for greenhouse application by using a GHE. The system was designed to handle low ambient temperature during the nighttime which affected the crops.…”
Section: Agricultural Greenhouse Coolingmentioning
confidence: 57%
“…An underground heat storage system in a double-film-covered greenhouse was designed on the basis of plant physiology to reduce the energy consumption in greenhouses. The results showed that the floor temperature was respectively 5.2°C, 4.6°C and 2.0°C higher than that of the soil in the adjacent reference greenhouse after heat storage in clear, cloudy and overcast sky in winter (Wang et al, 2006). Moreover, the temperature and humidity distribution of the canopy in double film solar greenhouse was studied based on computational hydrodynamics, and the simulation results showed high agreement with the measured values (Jiao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%